Uma abordagem geométrica da teoria de inversas generalizadas - Guimarães, Paulo Henrique Sales (2010)
A geometrical approach regarding to vectorial subspaces and linear projectors is used to present the Moore-Penrose generalized inversion theory. Its main properties are acquired by this method. Some properties of the normal equations are demonstrated as well. A generalization from this Moore-Penrose inverse geometric interpretation is applied to the reflexive inverses overall. The minimum square inverse is particularly demonstrated geometrically.